2018
DOI: 10.1002/er.4068
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cathode flow channel size and operating conditions on PEM fuel performance: A CFD modelling study and experimental demonstration

Abstract: Summary A comprehensive 3D, multiphase, and nonisothermal model for a proton exchange membrane fuel cell has been developed in this study. The model has been used to investigate the effects of the size of the parallel‐type cathode flow channel on the fuel cell performance. The flow‐field plate, with the numerically predicted best performing cathode flow channel, has been built and experimentally tested using an in‐house fuel cell test station. The effects of the operating conditions of relative humidity, press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…It can be observed from Figures that the difference between the values of highest current density in ECSSFF and triple serpentine is increasing as the RH of reactant gasses is increased. In general, all these trends of effect of %RH and temperature on the cell performance are qualitatively consistent with the studies reported by Ozen et al, Carcadea et al, and Zhang et al…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be observed from Figures that the difference between the values of highest current density in ECSSFF and triple serpentine is increasing as the RH of reactant gasses is increased. In general, all these trends of effect of %RH and temperature on the cell performance are qualitatively consistent with the studies reported by Ozen et al, Carcadea et al, and Zhang et al…”
Section: Resultssupporting
confidence: 91%
“…It can be observed from Figures 3-6 that the difference between the values of highest current density in ECSSFF and triple serpentine is increasing as the RH of reactant gasses is increased. In general, all these trends of effect of %RH and temperature on the cell performance are qualitatively consistent with the studies reported by Ozen et al, 30 Carcadea et al, 31 and Zhang et al 32 Figure 7A,B shows the I-V and I-P plots of the PEMFC with both the two flow field designs used on cathode side operated at a constant temperature of 70°C and different %RH of the reactant gas streams. It can be clearly seen from these figures that the ECSSFF exhibits superior performance especially at lower voltages in extending the power of drawing more current load.…”
Section: Performance Analysis Of Pemfc With Ecssff Design and Perfosupporting
confidence: 88%
“…Equation is the continuity equation where the calculate method of mixture density is provided in Equation . The source terms for the consumption of hydrogen, oxygen and the creation of water can be calculated by Equations , , and , respectively ()ρtrueu=SnormalH2+SO2+SH2O, ρmix=PitalicRTYiMi, SH2=Jitalican2FMH2, SO2=Jitalicca4FMO2, SH2O=+Jitalicca2FMH2O. …”
Section: Computational Detailsmentioning
confidence: 99%
“…This indicates that cell 33 is flooding, but cell 15 is not flooding. Increasing the velocity of the gas in the flow channel allows PEMFCs to perform better . The rapid flow of hydrogen enhances the mass transfer of hydrogen at the beginning of the purge process.…”
Section: Resultsmentioning
confidence: 99%